2008
DOI: 10.1159/000113895
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Endometrial Stromal Sarcoma with Florid Intravenous Component

Abstract: A case of low-grade endometrial stromal sarcoma (LGESS) with striking involvement of pelvic veins is reported. The pattern of vascular involvement resembled that seen in intravenous leiomyomatosis. The report illustrated that the possibility of venous involvement should always be considered in the management of LGESS. Search for tumor involvement of the venous system at the time of diagnosis of metastasis or recurrence is essential. Surgical management of extensive venous recurrence of LGESS is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…These emboli are mainly thrombotic and less frequently tumorous . However, PE occasionally exhibits both components, and such cases are termed pulmonary tumor thromboembolism (PTTE) . Most reported cases in the English language literature occurred after a cancer diagnosis, either before or after operative treatment of the cancer .…”
mentioning
confidence: 99%
“…These emboli are mainly thrombotic and less frequently tumorous . However, PE occasionally exhibits both components, and such cases are termed pulmonary tumor thromboembolism (PTTE) . Most reported cases in the English language literature occurred after a cancer diagnosis, either before or after operative treatment of the cancer .…”
mentioning
confidence: 99%
“…This was rather fortunate, as fatal congestive heart failure may be the initial presentation (8,20). In this case, elevation of serum liver enzymes was most likely caused by another reason, since it persisted even after tumor removal.…”
Section: Discussionmentioning
confidence: 82%
“…The key educational point of this case is that, although CT is widely performed, it is important to acknowledge the limitations of this method. It was previously reported that >50% of intravenous LG-ESS cases exhibited ICE (8). In such cases, the extent of the tumor should be determined using modalities such as MRI and ultrasonography, in addition to CT. MRI provides good soft tissue resolution and helps to distinguish an intravascular tumor from a non-tumor thrombus (16)(17)(18), whereas Doppler ultrasonography is also useful (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 22 cases of advanced LG-ESS have been reported in which the great vessels were invaded and a tumor of the inferior vena cava (IVC) formed [ 3 – 6 ]. However, earlier studies show that >50% of intravenous LG-ESS cases exhibit intracardiac extension [ 7 ].…”
Section: Introductionmentioning
confidence: 99%